Hoof balance and dealing with the major problems in practice - DIAKAKIS (Ν.ΔΙΑΚΑΚΗΣ) N.; MOUSTARDAS (Ν. ΜΟΥΣΤΑΡΔΑΣ) N.; DESIRIS (Α. ΔΕΣΙΡΗΣ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Hoof balance is one of the most important factors in the treatment of the lame horse. Quite often bad hoof conformation or poor hoof balance leads to or is closely connected to limb lameness. In this article some characteristic cases, in which the loss of hoof balance has led to lameness, are presented. Moreover the points which should characterize the balanced hoof after shoeing are presented. Finally, the corrective shoes that are most commonly used in practice are also presented.